KINERJA OPERATOR PADA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN KUBU RAYA - Dendy Partono E.42009080 (FISIP Universitas Tanjungpura Pontianak, 2013)
This research aims to identify and analyze the performance of the operator in carrying out their duties and obligations in order to make Family Register and ID card services in the Department of Population and Civil Registration Kubu Raya Regency. The title of this essay is based on less than optimal performance of operators so that excellent service not running optimally. This is exactly what causes the difficulty of the government in their policy because the data are less valid.Results of this study was, less optimal operator performance particularly in order to make Family Register and ID cards with an online system that is caused by the quality of human resources is still low. This can be assessed through Responsiveness is still low, Responsibility which has not been implemented properly and Accountability is still lacking. There are several factors that affect the performance and supervision of environmental factors. No punishment and rewards make workers do not have the motivation to work. Keywords: Operator Performance, Responsiveness, Responsibility and Accountability